The Central Única dos trabalhadores facing the labor reforms in Brazil: from Lula to Temer - Iglesias, Esteban (Universidad Nacional del Litoral, 2022)
This paper aims to analyze the variations in the political importance of the Central Única de los Trabajadores (CUT) from 2003 -when the Partido de los Trabajadores took over the national government-, to 2018 -when Michel Temer’s government ended-. All this is approached from the perspective of collective action and from the analysis of significant political processes for the period: the «Foro nacional del trabajo» -National Labour Forum- (2004-2008), the «Jornadas de Junio» -June Journeys- (2013), the «Ley de terciarización laboral» –Law on tertiarization of labour- (2015) y the «Reforma Laboral» –Labour reform- (2017). The main hypothesis is that the change in the political importance of the CUT is explained by its relationship with the PT. Thus, two stages have been identified: the 2004-2011 period of strong gravity and the 2013-2018 period of weak political gravity. In both periods, the political strategy of the CUT did not change substantially, combining institutional involvement with social mobilization. However, what changed was the political performance of the party in power, which had its peak during lulismo and then decline and crisis during the terms of Dilma Rousseff.